SUSTAINABLE WELFARE SOCIETY DENMARK – A ROLE MODEL FOR ENVIRONMENTAL POLICY (Contemporary Journal of Social Science Review, 2025)
This paper examines the concept of a sustainable welfare society, drawing on Denmark as an example. Where social quality and distributional justice are achieved through sustainable practices that respect the finite nature of natural resources and the environment. This study highlights how a nation can successfully balance economic development and environmental sustainability by adopting renewable energy sources, particularly wind energy and biofuels, to reduce greenhouse gas emissions and achieve absolute decoupling of economic growth from environmental harm. Despite significant advancement, this paper also explores the broader global implications of climate change and the challenges in aligning social policy with sustainability goals, particularly in the context of ASEAN nations, where financial, geographical, and regulatory barriers restrict the transition to cleaner, greener energy systems. The paper emphasizes the importance of public-private partnerships, policy frameworks, and innovative governance models in achieving the Sustainable Development Goals (SDGs) and ensuring a long-term, sustainable welfare state. Finally, it addresses the importance of reforms and global cooperation in overcoming the multifaceted challenges of energy transition, underscoring the need for a coordinated effort to foster green growth and tackle climate change on a global scale.